Kesediaan Mengadopsi Sistem Aplikasi Pengelolaan Keuangan Sekolah (Siperkasa) dengan Pendekatan Technology Acceptance Model - Titi Sugiarti; Oman Rusmana (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: To evaluate the variables that influence the user's desire to use the Siperkasa school financial application system at the school in the IX branch office of the Education and Culture Office of Central Java Province using the Technology Acceptance Model (TAM) approach. Research Methodology: This research is quantitative with a total sample of 106 and data is collected from surveys conducted online by application users via electronic forms. The data analysis method uses path analysis using AMOS software. The results of this study indicate that the behavioral intention to use Siperkasa is not influenced by the perceived interest and attitude towards its use. Ease of use has a positive effect on the recognition of the benefits of Siperkasa. Result: The results of this study are expected to contribute additional literature for the development of theories in public sector accounting, increase the ability to think about the phenomenon of using school financial management information systems, and can be considered in the development of an integrated school financial management information system (Siperkasa) and other accounting information systems in improving accountability, able to be accepted by users of Siperkasa, especially in schools within the Department of Education and Culture of Central Java Province. Limitation: This study has limitations, namely only using a sample of Siperkasa users in SMA/SMK/SLB Negeri in the IX branch office of the Education and Culture Office of Central Java Province.